Recordando o Passado by Aldo Krieger: Arrangement for seven-string guitar (Orfeu, 2017)
Memorial and score of Recordando oPassado by Aldo Krieger for seven-stringguitar, premiered at the 4ª Semana AldoKrieger in July 2016. The arrangement wascreated using as reference a recording anda book of scores with works of the composer, aiming at preserving the original melody and exploring features and idiomaticeffects of the instrument.
Keywords: Recordando o Passado; Aldo Krieger; Seven-string guitar